1987
DOI: 10.1073/pnas.84.24.8966
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, immunological, and immunocytochemical evidence for the association of chalcone synthase with endoplasmic reticulum membranes.

Abstract: Chalcone synthase [naringenin-chalcone synthase; malonyl-CoA:4-coumaroyl-CoA malonyltransferase (cyclizing), E.C. 2.3.1.74], the key enzyme of flavonoid pathways that was believed to be soluble, has been localized on ribosome-bearing endoplasmic reticulum membranes in the epidermis of buckwheat (Fagopyrum esculentum M.) hypocotyls. Enzyme activity measurement and immunoblots of buckwheat hypocotyl homogenates that were fractionated on linear sucrose density gradients and developed with a specific chalcone synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…The occurrence of multienzyme complexes in phenylpropanoid and flavonoid pathways is believed to explain how common intermediates in these pathways may lead to distinct metabolites. Different experimental approaches such as radioactive labeling, cell fractionation, or microscopic studies have suggested that enzyme complexes are structured on the ER, resulting in the channeling into a specific enzymatic reaction chain leading to a given final product (Czichi and Kindl, 1977;Hrazdina et al, 1987;Burbulis and Winkel-Shirley, 1999;Chen et al, 2011a). Distinct cytochrome P450 hydroxylases are involved in those pathways and serve as anchors of the metabolons to the ER membrane, as is likely the case for the sporopollenin metabolon evidenced in the present work.…”
Section: Discussionmentioning
confidence: 78%
“…The occurrence of multienzyme complexes in phenylpropanoid and flavonoid pathways is believed to explain how common intermediates in these pathways may lead to distinct metabolites. Different experimental approaches such as radioactive labeling, cell fractionation, or microscopic studies have suggested that enzyme complexes are structured on the ER, resulting in the channeling into a specific enzymatic reaction chain leading to a given final product (Czichi and Kindl, 1977;Hrazdina et al, 1987;Burbulis and Winkel-Shirley, 1999;Chen et al, 2011a). Distinct cytochrome P450 hydroxylases are involved in those pathways and serve as anchors of the metabolons to the ER membrane, as is likely the case for the sporopollenin metabolon evidenced in the present work.…”
Section: Discussionmentioning
confidence: 78%
“…As shown in Figure 8, this antibody recognizes a single protein species of approximately 42 kD in both -g and -r lines. This matches the size of chalcone synthase proteins isolated from a number of sources (Mol et al, 1983;Rail and Hemleben, 1984;Hrazdina, Zobel, and Hoch, 1987;Schmelzer, Jahnen, and Hahlbrock, 1988). The maximum signal is obtained from the soluble protein fraction of -r and -g plants (lanes 3 and 4), although low levels can be detected in the microsomal fractions (lanes 1 and 2).…”
Section: Chalcone Synthase Protein and Enzymatic Activitymentioning
confidence: 92%
“…It has been shown that a specific PAL isoform (PAL1) is physically associated with both isolated microsomes and the cytoplasmic fraction in fractionated tobacco cell extracts, supporting a model in which PAL associates with MECs in an isoform-specific manner to modulate a carbon flux into specific downstream pathways (12). Other data from experiments employing classical approaches such as double radioactive labeling assays (13)(14)(15), enzyme co-purification (15,16), and immunohistochemical localization (17) support the presence of MECs among enzymes in the entry point or downstream pathways. Investigation of possible MECs in phenylpropanoid metabolism has been further pursued in recent years using various molecular techniques, revealing direct proteinprotein interactions among enzymes in the flavonoid pathway in Arabidopsis (18) and the elicitor-dependent endoplasmic reticulum (ER)-localization of an otherwise cytosolic isoflavone Omethyltransferase in alfalfa (19).…”
mentioning
confidence: 99%